THE EFFECTS OF SERVICE QUALITY ON TOURISTS SATISFACTION IN FORT ROTTERDAM MAKASSAR - Takka, Muhammad Azwan; Abdul Wahid; Indrawaty Asfah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
The purpose of this study is to investigate the effect of service quality on tourist satisfaction in Fort Rotterdam, Makassar. The main population of this study consists of 30 tourists. A study using aggregate sampling theory used a sample size of 30 people. Data collection was done by distributing questionnaires using descriptive methods. The analysis involved the application of simple linear regression using statistical tools. The research results show a positive and significant effect of the variable quality service on the satisfaction of the tourist with a significance value of 0.001 and a coefficient of 0.405. The test results show a calculated t-value of 5.461, which exceeds the critical t-table value of 2.030. This leads to the conclusion that there is a positive and significant relationship between service quality and tourist satisfaction at Fort Rotterdam in Makassar. The effect of service quality on tourist satisfaction is 46%, the remaining 54% is influenced by unknown or unexamined variables in this study.